The Use of Social Media as A Medium For Disseminating Academic Information - Fitria Claudya Lahinta; Michael Efraim Maensiga; Gabriel Kenshi Kaawoan; Villy Ijilia Christanti Bawereng; Zefanya Agustina Popy Pondaag (Publikasi Indonesia, 2026)
Background: Higher education institutions face increasing pressure to disseminate academic information efficiently to academic communities dominated by digital-native generations. Traditional communication channels such as notice boards, institutional emails, and printed announcements are often considered slow, limited in reach, and less aligned with contemporary communication habits. Objective: This study aims to analyze the level of adoption and preference for using social media as a source of academic information, evaluate the effectiveness of platforms such as Instagram, X (formerly Twitter), and Facebook in enhancing reach and delivery speed, and identify key challenges related to credibility, interaction management, and the risk of misinformation. Methods: A quantitative approach was employed through a survey involving 450 respondents representing students, lecturers, and administrative staff at University X. The survey was complemented by a six-month content analysis of the institution’s official social media accounts (January–June 2024). Data were analyzed using descriptive statistics and simple regression. Results: Findings indicate that 88% of students and 72% of lecturers/staff rely on social media as their primary source of academic information. Average monthly reach on social media was significantly higher than the open rate of academic emails. Regression results reveal a significant positive correlation between posting frequency and perceived communication effectiveness. Conclusion: In conclusion, social media is an exceptionally effective tool for fast and wide academic communication. However, the study emphasizes that integrated governance linking social media with formal communication channels such as institutional websites is essential for ensuring information credibility and minimizing misinformation risks.